PROBLEMS WITH WATER RESOURCES - Djumanazarova Altingul Tengelovna; Imyaminova Risolat Noman kizi; Khudaynazarova Gozzal Perdebaevna (Scholar Express Journals, 2025)
The article analyzes the use of water resources in agriculture in Uzbekistan and its current state. It focuses on the problems of accelerating the use of water-saving technologies in crop cultivation to solve the problem of water scarcity.
Keywords: Water shortage problems; water-saving irrigation; watering